Situation Report: Romania, 12 July 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Military Delegation Received by Khrushchev Third Session of Czechoslovak-Romanian Mixed Economic Commission Romania's Activities within Comecon Reaction to Sino-Soviet Dispute Miscellaneous